Assessment of sources and utilization of funding of state universities and colleges - Rosario G. Manasan; Ma. Laarni D. Revilla (Philippine Institute for Development Studies (PIDS), 2015)
The implementation of the "Higher Education Modernization Act of 1997", CHED Memorandum Order No. 20, and "Public Higher Education Reform Framework" granted state universities and colleges (SUCs) the right to corporatize and manage their own incomes. Given these laws and rules, an assessment/review on the income collection and utilization of SUCs has become mandatory. This study aims to review the specific sources of internally generated incomes (IGI) of SUCs and analyze how these incomes are allocated and utilized. It also evaluates the shares of the national government subsidy and IGI in terms of collection and usage. The study is intended to provide some guidance on how to increase SUCs` IGI and ensure that the utilization of the same is focused on their instruction, research and extension activities in a manner that is complementary with the regular subsidy provided to SUCs by the national government. The study, however, does not cover an issue, which is just as important, if not more so, on the accuracy and integrity of the SUCs` Financial Accountability Reports (as submitted to the DBM).
Keywords: 330; state universities and colleges (SUCs); income utilization; national government subsidies; internally generated income; receipts; expenditures; income generating projects (IGPs); special trust fund; revolving fund